Exploring the relationships between motivation, attachment and loyalty within sport event tourism. Issue 1 (2nd January 2017) - Kirkup, Naomi; Sutherland, Matthew
Abstract : Attendance at sports events continues to rise, as evidenced by increased attendance across a range of sports events in 2014. Despite this, destinations that host live sports events struggle to attract repeat visitors outside scheduled events. This study aims to better understand the relationship between motivation, attachment and loyalty within event tourism. This paper discusses the existing contributions in these areas by drawing on sport and tourism literature and is the first to investigate the relationship across all three constructs. Within this paper, we develop the initial outline of a theoretical model, which depicts these relationships.